Daring to tap external strategic resources: competitive advantage in global industries. Issue 3 (9th May 2019) - Orr, Stuart
Abstract : Purpose: In addition to their internal resources, companies in most industries rely upon external strategic resources to maintain and improve their performance. External strategic resources have a similar effect on competitiveness but are located in the company's networks or even in unrelated industries. Some companies underuse these resources, while other companies focus too strongly on accessing external resources in their own industry, which results in hyper-competition. This paper aims to explain how different industries use external resources and describes the criteria for a balanced approach which leads to knowledge transfer, diversity and supports the development of new business. Design/methodology/approach: Examples and evidence from four different industries are used to identify the different approaches for accessing external strategic resources. Findings: Valuable external strategic resources are non-transferable, located in a complementary product organisation, knowledge-oriented, located in a different country, preferably not part of the organisation's primary external focus (e.g. supply chain), able to introduce diversity and innovation and are compatible with network behaviours. Practical implications: External strategic resources are frequently found within the organisation's supply chain, however, use of these resources should be balanced by external resources from non-related industries to increase diversity and reduce the likelihood of hyper-competition. Originality/value: This paper explains why external strategic resources are valuable, identifies the different approaches to accessing them, describes the benefits and drawbacks associated with each approach and provides the key criteria for identifying a valuable external strategic resource.